Aid Quality and Donor Rankings - Knack, Stephen; Rogers, F. Halsey; Eubank, Nicholas (2012)
This paper offers new measures of aid quality covering 38 bilateral and multilateral donors, as well as new insights about the robustness and usefulness of such measures. The 2005 Paris Declaration on Aid Effectiveness and the follow-up 2008 Accra Agenda for Action have focused attention on common donor practices that reduce the development impact of aid. Using 18 underlying indicators that capture these practices -- derived from the OECD-DAC's Survey for Monitoring the Paris Declaration, the new AidData database, and the DAC aid tables -- the authors construct an overall aid quality index and four coherently defined sub-indexes on aid selectivity, alignment, harmonization, and specialization. Compared with earlier indicators used in donor rankings, this indicator set is more comprehensive and representative of the range of donor practices addressed in the Paris Declaration, improving the validity, reliability, and robustness of rankings. One of the innovations is to increase the validity of the aid quality indicators by adjusting for recipient characteristics, donor aid volumes, and other factors. Despite these improvements in data and methodology, the authors caution against overinterpretation on overall indexes such as these. Alternative plausible assumptions regarding weights or the inclusion of additional indicators can still produce marked shifts in the ranking of some donors, so that small differences in overall rankings are not meaningful. Moreover, because the performance of some donors varies considerably across the four sub-indexes, these sub-indexes may be more useful than the overall index in identifying donors relative strengths and weaknesses.